Outcomes of displaced adolescent distal third tibia fractures: can we do better?. Issue 2 (19th July 2021) - Ramalingam, Wendy G.; Carry, Patrick; Brazell, Christopher; Calkins, Ryan; Linza-Moscati, Sara; Stoneback, Jason; Miller, Nancy Hadley
Abstract : Because adolescent distal third tibia fractures pose treatment challenges, we aimed to identify factors predictive of failure among common treatment methods: casting without manipulation, closed reduction and casting (CRC) and open treatment. Among displaced fractures, we compared outcomes between CRC versus open treatment. Skeletally immature individuals (10–17 years) with extra-articular distal third tibia fractures at a level 1 trauma center (2011–2017) were retrospectively reviewed. Patient demographics, injury and treatment characteristics and complications were recorded. Radiographs were evaluated for unacceptable alignment (angulation >5°, translation >50%, and shortening >1 cm) and time to union. Of 140 individuals, casting was the most common treatment method ( n = 81), followed by CRC under anesthesia/sedation ( n = 38), and open treatment ( n = 34). For fractures casted without manipulation, increased fracture severity based upon our novel grading system [hazard ratio (HR): 10.5, 95% CI, 4.2–27.5, P < 0.0001] was significantly related to treatment failure. Outcomes for a selected group of 47 initially displaced fractures (33 CRC and 14 open treatments) were evaluated. For CRC, 9 (27.3%) healed with malunion and 6 (18.2%) failed initial CRC, resulting in a treatment failure rate of 36.7%. For open treatment, 2 (14.3%) underwent hardware removal, 2 (14.3%) healed with malunion and one developed infection requiring reoperation. No fractures healed with malunion required surgical correction during the study period. The odds of persistent malalignment in CRC was 3.77 [95% CI, 0.44–32.60, P = 0.2274] times open treatment. Adolescent minimally displaced distal tibial fractures can undergo successful treatment with casting. However, displaced fractures have a higher chance of short-term failure with CRC. Close monitoring of displaced fractures in the adolescent is essential during conservative management.